Odpowiedź :
Cześć!
a)
[tex]3(x-y)=3\cdot x-3\cdot y=\boxed{3x-3y}\\[/tex]
b)
[tex]4(a+b)=4\cdot a+4\cdot b=\boxed{4a+4b}\\[/tex]
c)
[tex](2x-y)\cdot(-2)=2x\cdot(-2)-y\cdot(-2)=\boxed{-4x+2y}\\[/tex]
d)
[tex]-5(-3q+2+b)=-5\cdot(-3q)-5\cdot2-5\cdot b=\boxed{15q-10-5b}\\[/tex]
e)
[tex](-2x+y-1)\cdot4=-2x\cdot4+y\cdot4-1\cdot4=\boxed{-8x+4y-4}\\[/tex]
f)
[tex]-3(3-2xy+5y)=-3\cdot3-3\cdot(-2xy)-3\cdot5y=\boxed{-9+6xy-15y}\\[/tex]
a) 3(x-y) = 3x - 3y
b) 4(a+b) = 4a + 4b
c) (2x-y)*(-2) = -4x + 2y
d) -5(-3q+2+b) = 15q - 10 - 5b
e) (-2x+y-1)*4 = -8x + 4y - 4
f) -3(3-2xy+5y) = -9 + 6xy - 15y